Porphyromonas gingivalis Gingipains and Adhesion to Epithelial Cells - Chen, Tsute (American Society for Microbiology, 2001)
Porphyromonas gingivalis is one of the principal organisms associated with adult periodontitis. Bacterial surface proteins such as fimbriae and gingipain hemagglutinin domains have been implicated as adhesins that actuate colonization of epithelium lining the gingival sulcus. We investigated the genetics of P. gingivalis adhesion to monolayers of epithelial cells using wild-type and gingipain mutant strains. These experiments suggested that arginine-specific gingipain (Rgp) catalytic activity modulated adhesion. From the data obtained with rgp mutants, we constructed a working hypothesis predicting that attachment and detachment of P. gingivalis to epithelial cells were mediated by gingipain adhesin and Rgp catalytic domains, respectively. A membrane-based epithelial cell binding assay, used to locate adhesins in extracellular fractions of wild-type and mutant strains, recognized gingipain peptides as adhesins rather than fimbriae. We developed a capture assay that demonstrated the binding of gingipain adhesin peptides to oral epithelial cells. The adherence of fimbrillin to epithelial cells was detected after heat denaturation of cell fractions. The prediction that Rgp catalytic activities mediated detachment was substantiated when the high level of attachment of an rgp mutant was reduced in the presence of wild-type cell fractions that contained gingipain catalytic activities.